2019
DOI: 10.1016/j.fcr.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a simulation model for hairy vetch (Vicia villosa Roth) self-regeneration under different crop rotations

Abstract: Hairy vetch (Vicia villosa Roth) is a winter annual legume cultivated for both seed production and pasture grazing in rotation with cereal crops. Vicia villosa increases N concentrations in the soil, thus contributing to the sustainability of semiarid regions. Other important advantage of hairy vetch is associated with the capability for natural reseeding in the pasture phase. Although the benefits of hairy vetch can be significant, its adoption could become a problematic volunteer weed in the cereal phase. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…An additional challenge of HV is seed dormancy control, which can lead to incomplete emergence after seeding (Jacobsen et al, 2010;Maul et al, 2011). On the contrary, in agroecosystems of semiarid regions, HV natural reseeding capacity is a desirable trait reducing establishment costs (Renzi et al, 2017;Renzi et al, 2019), especially when used as forage crop by livestock farmers.…”
Section: Introductionmentioning
confidence: 99%
“…An additional challenge of HV is seed dormancy control, which can lead to incomplete emergence after seeding (Jacobsen et al, 2010;Maul et al, 2011). On the contrary, in agroecosystems of semiarid regions, HV natural reseeding capacity is a desirable trait reducing establishment costs (Renzi et al, 2017;Renzi et al, 2019), especially when used as forage crop by livestock farmers.…”
Section: Introductionmentioning
confidence: 99%
“…However, these genotypes would not be suitable in ley farming practice, in which the success of annual crop rotation depends on the ability to provide an adequate plant density for seed/forage production by self-regeneration from the soil seedbank. On the contrary, from a weed management perspective, we observed that in HV genotypes with more than 70% of initial PY, the problem of "volunteer plants" can be avoided if management practices avoid seed production and seedbank replenishment for at least three consecutive years [17]. The selection breeding of cultivars with <14% and <8% of initial PY could reduce this period further to one year and 6 months, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…The most important traits for which HV has been selected include biomass production and a low level of seed dormancy [13]. Low PY is a desirable trait for stand establishment [8], while incomplete germination related to PY can result in soil seed bank formation and emergence in subsequent crop rotations as a problematic weed [8,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many Mediterranean CWR seed physical dormancy has been selected as bet-hedging against false breaks (heavy rainfall that precedes the growing season start and which would expose the recently germinated seedling to extreme heat and drought) and other disturbances such as catastrophic herbivory ( Piano et al, 1996 ; Norman et al, 2002 ; Smýkal et al, 2014 ; Berger et al, 2017 ). Typically, there is wide ranging dormancy within populations ( Berger et al, 2017 ; Hradilová et al, 2019 ; Renzi et al, 2019 ), that in combination with variable seed placement will drive staggered germination across the CWR population over the growing season, exposing individuals to different micro-habitats in space and time.…”
Section: Context: How and Why Do Crops And Their Wild Relatives Differ?mentioning
confidence: 99%